2022
DOI: 10.1007/s11625-022-01191-2
|View full text |Cite
|
Sign up to set email alerts
|

Commoning the governance: a review of literature and the integration of power

Abstract: The concept of commoning is continuing to gain scholarly interest, with multiple definitions and interpretations across different research communities. In this article, we define commoning as the actions by groups with shared interests towards creating shared social and relational processes as the basis of governance strategy. Perhaps it can be more simply defined as collective ways of relating and governing. This article addresses two specific gaps in the commoning literature: (1) to bridge disparate strands … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…They identify four ASs central to collective action in climate adaptation in each of the studied islands and found that few strategic actors involved in all situations lead to reinforcing arrangements. Partelow and Manlosa (2022) introduce a process-based, relational perspective of commoning to structuralist analysis of NAS. They argue that merging the analysis of commoning and associated power with the analysis of NAS requires epistemic pluralism because power structures human relations in many ways.…”
Section: Key Themes Across Contributionsmentioning
confidence: 99%
See 2 more Smart Citations
“…They identify four ASs central to collective action in climate adaptation in each of the studied islands and found that few strategic actors involved in all situations lead to reinforcing arrangements. Partelow and Manlosa (2022) introduce a process-based, relational perspective of commoning to structuralist analysis of NAS. They argue that merging the analysis of commoning and associated power with the analysis of NAS requires epistemic pluralism because power structures human relations in many ways.…”
Section: Key Themes Across Contributionsmentioning
confidence: 99%
“…Actor-network theory can add to NAS, because it helps to explore relations of both human and non-human objects in mid-range explanations of institutional change in NAS (Hurlbert and Akpan 2022). Also, the commoning perspective is centred around unfolding relationships that can take non-human objects and their context into account in process analysis of socio-ecological issues (Partelow and Manlosa 2022).…”
Section: Nas In a Relational Turnmentioning
confidence: 99%
See 1 more Smart Citation
“…The factual form of commoning is heavily dependent on the circumstances (e.g., cultures, societal structures, time, space, physical attributes) and on learned behaviours as well as thinkable narratives." Simply put, commoning can be defined "as the actions by groups with shared interests towards creating shared social and relational processes as the basis of governance strategy," as articulated by Partelow & Manlosa (2022). Partelow & Manlosa (2022) present examples where "commoning the commons" is more viable when users can economically leverage existing resources (Partelow & Manlosa, 2022).…”
Section: Horizontal Approach To Institutions/rules: Design Principles...mentioning
confidence: 99%
“…Simply put, commoning can be defined "as the actions by groups with shared interests towards creating shared social and relational processes as the basis of governance strategy," as articulated by Partelow & Manlosa (2022). Partelow & Manlosa (2022) present examples where "commoning the commons" is more viable when users can economically leverage existing resources (Partelow & Manlosa, 2022). Partelow & Manlosa (2022) offered two such examples: tourism governance on Gili Trawangan in Indonesia and aquatic food production systems in Bulacan, Philippines.…”
Section: Horizontal Approach To Institutions/rules: Design Principles...mentioning
confidence: 99%